Antibacterial Activity of Endophytic Bacteria from Butterfly Pea (Clitoria ternatea L.) Root against Staphylococcus aureus and Escherichia coli - Polandos, Chersa; Fitriani, Any (Bioeksperimen: Jurnal Penelitian Biologi, 2025)
Indonesia is rich in biodiversity, with many medicinal plants such as Clitoria ternatea (butterfly pea) known for antibacterial properties. This study aimed to evaluate the antibacterial activity of ethyl acetate extracts from endophytic bacteria isolated from C. ternatea roots, with potential application in developing natural antibacterial agents. The bacteria were identified as belonging to the genera Bacillus, Pseudomonas, and two strains of Azomonas (A and B). Extracts were tested against Staphylococcus aureus and Escherichia coli using Disk Diffusion Assay (DDA), Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), and Time-Kill assays. Results showed Pseudomonas extract at 40 mg/ml had the largest inhibition zone against S. aureus (6.75 ± 0.353 mm), while Azomonas A was most effective against E. coli (3.187 ± 0.618 mm). The lowest MIC against S. aureus was 2.5 mg/ml from Azomonas B, with MBCs of 20 mg/ml for Pseudomonas and Azomonas B. Against E. coli, Azomonas A showed MIC and MBC of 10 mg/ml and 40 mg/ml, respectively. Time-Kill assays confirmed bacterial reductions at MIC and higher concentrations. These findings suggest C. ternatea’s endophytic bacteria extracts have promising antibacterial potential for sustainable medicinal use.